O uso de técnicas de sensoriamento remoto na identificação de formas na região de Porto Rico, planície de inundação do Alto Rio Paraná, MS/PR - Andrade, Ismar Renan Alves de (2008)
Floodplains are forms originated by the fluvial action and can have different definitions according the approach of the study. Nanson and Croke (1992), in their genetic classification say that it is a alluvial form, separated from its channels by margins and constructed by river's transported sediments, this environment are characterized by the diversity of environments the complete them (lótics, lentics, and terrestrial), this environments are submitted periodically to distinct conditions (aquatic and terrestrials). The need grow up the knowledge about the Upper Paraná River Floodplain goes through matters of simply concept, like a need to have a clear referential, that is, an information source regardless the topographics features to evaluate of its hidrodinamic operation. Thus, the aim of this study is to identify the landforms at the Upper Paraná River Floodplain in the neighborhoods of Porto Rico, by the using of topographic models get from geoprocessing techniques. The study unity is located at the Porto Rico region and comprises the are situated at the left margin of Paraná River, between the mouth of Paranapanema River and the first mouth of Ivinheima River (Ipoitã channel). The nearly localities are the city of Porto Rico and the district of Porto São José, at Paraná's side,at Mato Grosso do Sul side, the communities are more than 15 Km away distant from the margin of Paraná River. To do this work, was used Remote Sensing techniques that allowed inferred on the study area. The identification of landforms at the floodplain was possible through the generation of products like Digital Elevation Models (SRTM and ASTER) classification of orbital images, and generation of the trend surface and the residuals o the study area furthermore, fields observations were maded. The application of the method allowed to do some considerations regarding the efficiency of the products of Remote Sensing for identifying landforms in areas such as the present study. The Digital Elevation Models were satisfactory in the identification of forms in general and detail scales, but some care should be taken not to and work in too small scales, especially when using the SRTM DEM. Maps of trend surface and residuals also allowed that considerations were made about the behavior of plain against of flooding. Analyses of products allowed finds that the plain is cut by a series of structural blocks and low blocks that create environments for easier penetration of water in the plains, such as the area of the rivers Curuuba and Ivinheima. The blocks create high areas of greatest difficulty for the entry of water, restricting the floods to the lowest areas